The Construction of Sectarianism: How Intermestics shaped “Other”ing in Iraq and Syria - Elrashidy, Dina (AUC Knowledge Fountain, 2016)
This thesis applies a social Constructivist lens to the outbreak of sectarian conflicts in Iraq and Syria, the two countries in the Middle East which have seen an outbreak of violent civil wars in the past decade. The dominant explanations for these conflicts reduce the issue down to identities. This isn’t surprising given the diversity of the two states’ populations. What we aim to assess in this thesis is how these sectarian identities have been shaped and constructed. I refute the notion that sectarianism is a natural outcome of competing identities and religious myth-symbols. Instead, I explore the question of how intermestics, or what Bahgat Korany defines as “the organic relationship between the international and the domestic,” shaped the sectarian conflicts that broke out in Syria and Iraq. The outcome of this research, which will be touched on in its conclusion, will put forth the common elements which have shaped the Iraqi and Syrian sectarian conflicts. Such analyses can be used to better understand the potential dangers of future sectarian strife in the region. Furthermore, the argument of this thesis highlights the importance of looking at the complex dynamics of intermestics in international relations.